Les migrations en transit au Maroc. Attitudes et comportement de la société civile face au phénomène - Laura Feliu Martínez (L’Année du Maghreb)
For thousands of migrants from sub-Saharan Africa, Morocco is the last step on the journey to Europe. This paper analyzes the attitudes of key Moroccan political and social actors. Responsiveness and variability on the part of Moroccan authorities highlight the double dependence of a management process focused on security issues yet influenced by external pressures, including the fragile compromise with the European Union and some member countries. For some years Moroccan associations interested in this phenomenon have been attending to their deficiencies in training, knowledge and the monitoring of in-transit sub-Saharan migrants.